2023
DOI: 10.1037/pspa0000333
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental goal activation increases online petition support across languages.

Abstract: Research on processing fluency and instrumental goal activation suggests people often perceive complex information positively when effort in a task is valued. The current article evaluates this idea in five online petition samples (total N = 1,047,655 petitions and over 200 million words), assessing how the linguistic fluency of a petition associates with support. Consistent with prior work, petitions with lower rates of lexical fluency (fewer common words) associated with more signatures and an increased prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 102 publications
2
18
0
Order By: Relevance
“…4 Scores on this index range from 0 (low on analytic writing) to 100 (high on analytic writing) are "converted to percentiles based on standardized scores from large comparison corpora" (Boyd et al, 2022). High scores tend to reflect formal and complex writing styles compared to low scores (Markowitz, 2022), which tend to reflect more narrative writing styles (Pennebaker et al, 2014). Second, style was evaluated with adjectives (e.g., words such as funny, quiet), which consider the descriptive style of one's text.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Scores on this index range from 0 (low on analytic writing) to 100 (high on analytic writing) are "converted to percentiles based on standardized scores from large comparison corpora" (Boyd et al, 2022). High scores tend to reflect formal and complex writing styles compared to low scores (Markowitz, 2022), which tend to reflect more narrative writing styles (Pennebaker et al, 2014). Second, style was evaluated with adjectives (e.g., words such as funny, quiet), which consider the descriptive style of one's text.…”
Section: Methodsmentioning
confidence: 99%
“…Readability is broadly calculated by counting the number of words per sentence and syllables per word, with longer sentences and longer words being less readable (e.g., more complex) than shorter sentences and shorter words. The Flesch Reading Ease measure has been applied to scientific articles (Markowitz & Hancock, 2016), online petitions (Markowitz, 2022), and social media data (Hubner & Bond, 2021) to assess the structural complexity of language patterns. Descriptive statistics across variables are in the top panel of Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Markowitz (2019) also identified that National Science Foundation grant abstracts written in a more complex manner (e.g., more words, more jargon, more words per sentence) received more money from the NSF than those written in a less complex manner. Finally, online petitions written in a more complex, less fluent manner (e.g., fewer common words, more analytic writing, less readable writing) received more online supporters than online petitions written in a less complex, more fluent manner (Markowitz, 2022). Together, while simplicity is often preferred in effortless tasks, complexity can be favored when effort is instrumental to goal attainment (Briñol et al, 2006;Labroo & Kim, 2009).…”
Section: Processing Fluency: Is Simpler Always Better?mentioning
confidence: 96%
“…There are three types of linguistic fluency often evaluated based on prior work (Markowitz, 2022): lexical fluency, analytic writing fluency, and structural fluency. Lexical fluency considers the ease or difficulty associated with understanding words based on how common they are in everyday English.…”
Section: The Current Papermentioning
confidence: 99%
See 1 more Smart Citation